MASA JABATAN LEMBAGA LEGISLATIF DI INDONESIA GUNA MENEGAKAN PRINSIP KONSTITUALISME - Hamrin, Hamrin; Endratno, Cucuk (NATIONAL JOURNAL of LAW, 2022)
People's representative institutions in the Indonesian constitutional systemconsist of the People's Consultative Assembly (MPR), the People's RepresentativeCouncil (DPR), the Regional Representatives Council (DPD), the RegionalPeople's Representative Council (DPRD) both provincial and district/city. As apeople's representative institution, members of the MPR, DPR, DPD, ProvincialDPRD and Regency/Municipal elected by the people through general elections.General elections are held in a direct, general, free, secret, honest and fair mannerevery five years. The objectives to be achieved in writing this dissertation are toanalyze and determine the regulation of the tenure of legislative members in theconstitutionalism system in Indonesia and to analyze and find the concept of theterm of office of legislative members in Indonesia in order to enforce theConstituent Principles.This study uses a normative juridical approach that emphasizes libraryresearch. In this research, the Legislation approach, conceptual approach,comparative approach, case approach, historical approach, and philosophicalapproach are used. Types of legal materials used are primary, secondary, andtertiary legal materials. The analysis used is qualitative descriptive analysis.The results show that the House of Representatives is neededlimitation ofterm of office, because the term of office is the same as the term of office of thePresident as stated in Article 7 of the 1945 Constitution. The limitation ofperiodization is meant by considerations: guaranteeing human rights, avoidingarbitrariness of members of the people's representative institutions, creatingthought innovation institutions in institutions people's representatives. The idealconcept of limiting the term of office of the DPR and DPD, it is advisable to revisethe MD3 Law; second, to propose the concept of limiting the term of office ofmembers of the DPR and DPD based on a constitutional democracy perspective, itis advisable to revise the addition of paragraphs in Articles 76 and 252 of the MD3Law, regarding the affirmation of how many years in office are considered one termfor both DPR and DPD. It is also necessary to revise Article 76 Paragraph (4) andArticle 252 Paragraph (5) of the MD3 Law, relating to the concept of limiting theterm of office to only two terms.